FEATURES OF OUTFLOW OF INTRAOCULAR LIQUID AFTER AN EKSIMERLAZER SKLEREKTOMY (PILOT STUDY) - E. A. Korchuganova; O. A. Rumyantseva; S. B. Gudkova (Oftalʹmologiâ)
Modern approaches to surgical glaucoma treatment is based on the safe and effective methods. In recent years, great attention is paid to the techniques of stimulating uveoscleral path outtake aqueous humor from the eye. Uveoscleral space in the extended outflow pathways is dominant and constitutes about 72%. Sclera is a field of the greatest interest, as the end stages of the outflow of aqueous humor via the uveoscleral path. The aim of the study was to investigate the influence of excimer laser sclerectomy on the drainage function of the eye and development of a mathematical model based on the permeability of the sclera of the amount of laser ablation at a defined area of laser exposure and the level of IOP. Studies were conducted on 12 human cadaver eyes isolated person. The domestic excimer laser “MicroScan Vizum” with a wavelength of 193нм (0,193 µm) was used for the thinning of sclera. In the experiment used a special computer program provided ablation of scleral tissue, the scleral bed forming a rectangular shape with a size 7,0x5,0 mm. the Depth of influence started from 100 microns to 600 microns in increments of 50 µn. The exposure was carried out at a constant perfusion pressure of 25 mm Hg After each impact was measured of the coefficient ease the outflow. A correlation was established between the factor and effective features, i.e., between the excimer laser deep sclerectomy (µm) and ratio of lightness outflow (mm3/min/mm Hg.St). Thinning of the sclera leads to an improvement of its permeability and increasing the coefficient ease the outflow. A mathematical model, allowing to achieve the desired ratio of lightness outflow experiment by excimer laser sclerectomy was developed. The mathematical model has the form of the regression equation.The sclera is a promising object for further developments in the surgical treatment of glaucoma. Laser ablation of the sclera leads to an improvement of outflow via the uveoscleral path and reduce intraocular pressure.